Growth of vanilla cuttings under modified acid soil media and application of several plant growth regulators - Kurniawan, Rifqi Raditya; Ahadiyat, Yugi Rahayu; Tini, Etik Wukir (Universitas Padjadjaran, 2026)
This research aimed to optimize the growth of vanilla (Vanilla planifolia) cuttings in acid soils by modifying the growing media and applying several types of plant growth regulators (PGRs). Several types of PGRs, including synthetic compounds such as indole-3-acetic acid (IAA) and 6-benzylaminopurine (BAP), as well as natural extracts from shallot (Allium ascalonicum L.) and moringa leaves (Moringa oleifera), were tested to enhance plant performance in acid-growing conditions. The primary objectives were to determine the optimal soil amendment formula and the most effective PGR type for promoting vanilla growth, and to develop a measurable, easy-to-use PGR formulation accessible to farmers. The study was conducted experimentally using a randomized complete block design (RCBD) with the first factor being modified acid soil media and the second factor being the type of PGRs. The results showed that both 100 ppm BAP (Z2) and 10% shallot extract (Z3) significantly outperformed other PGR treatments across all parameters and observation times. For instance, Z2 produced the highest recorded values for internodes (15.11 internodes) at 90 DAP, number of leaves (10.26 leaves) at 60 DAP, total leaf area (413.74 cm²) at 90 DAP, and aerial roots (12.22 roots) at 90 DAP. Conversely, Z3 demonstrated superior performance in the number of leaves (15.56 leaves) at 90 DAP and total leaf area (421.95 cm²) at 90 DAP. This treatment can be recommended as an effective strategy for enhancing the establishment of vanilla cuttings in acidic soil conditions.